Physeteroidea (Cetacea: Mammalia) hyper-diversification from late Miocene of South Pacific, new fossils from the Sacaco area, Arequipa, Peru - Benites-Palomino, Aldo (2020)
Sperm whales (Physeteroidea) are a group of cetaceans with a restricted modern ecology. The three extant species are a remnant of a group that reached its diversity peak during the Miocene, including five already-described species from the Pisco Formation, Ica-Arequipa, Peru. We report two isolated teeth from the upper Miocene localities of Sacaco and Sud-Sacaco, which correspond with the typical morphology of Physeteridae. This morphology is similar to the one present in northern hemisphere taxa as Orycterocetus or Aulophyseter. Because of this the remains could be related to physeterids with piscivorous habits, so there would not be a niche overlap with other coeval sperm whales. This new registry expands the fossil cetacean community of Sacaco, which was favored by the great diversity of shallow environments that dominated the Peruvian coast until the final establishment of the Humboldt System.